Apelin Does Not Impair Coronary Artery Relaxation Mediated by Nitric Oxide-Induced Activation of BKCa Channels - Mughal, Amreen; Sun, Chengwen; O’Rourke, Stephen T. (Frontiers in Pharmacology, 2021)
Apelin-APJ receptor signaling regulates vascular tone in cerebral and peripheral arteries. We recently reported that apelin inhibits BKCa channel function in cerebral arteries, resulting in impaired endothelium-dependent relaxations. In contrast, apelin causes endothelium-dependent relaxation of coronary arteries. However, the effects of apelin on BKCa channel function in coronary arterial myocytes have not yet been explored. We hypothesized that apelin-APJ receptor signaling does not have an inhibitory effect on coronary arterial BKCa channels and hence does not alter nitric oxide (NO)-dependent relaxation of coronary arteries. Patch clamp recording was used to measure whole cell K+ currents in freshly isolated coronary smooth muscle cells. Apelin had no effect on the increases in current density in response to membrane depolarization or to NS1619 (a BKCa channel opener). Moreover, apelin did not inhibit NO/cGMP-dependent relaxations that required activation of BKCa channels in isolated coronary arteries. Apelin-APJ receptor signaling caused a marked increase in intracellular Ca2+ levels in coronary arterial smooth muscle cells, but failed to activate PI3-kinase to increase phosphorylation of Akt protein. Collectively, these data provide mechanistic evidence that apelin has no inhibitory effects on BKCa channel function in coronary arteries. The lack of inhibitory effect on BKCa channels makes it unlikely that activation of APJ receptors in coronary arteries would adversely affect coronary flow by creating a vasoconstrictive environment. It can be expected that apelin or other APJ receptor agonists in development will not interfere with the vasodilator effects of endogenous BKCa channel openers.